2002
DOI: 10.1046/j.1365-2591.2002.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro evaluation of four materials as barriers to coronal microleakage in root-filled teeth

Abstract: None of the materials were able to prevent microleakage in all specimens. Vidrion R and Scotch Bond demonstrated the poorest results when used as barriers to coronal microleakage, whilst IRM and Coltosol were significantly better in preventing microleakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 21 publications
4
45
0
15
Order By: Relevance
“…Current restorative dentistry researches using GIC assess different ways to avoid the gaps in the tooth-restorations interface, which, according to some authors, it is still not well considered [22,23]. Results from this study indicate a better behavior in terms of microleakage scores for the water group in both GIC tested materials but the same trend was not seen for the orange juice and Coca-Cola groups, possibly due to the low pH in this beverages.…”
Section: Discussionmentioning
confidence: 65%
“…Current restorative dentistry researches using GIC assess different ways to avoid the gaps in the tooth-restorations interface, which, according to some authors, it is still not well considered [22,23]. Results from this study indicate a better behavior in terms of microleakage scores for the water group in both GIC tested materials but the same trend was not seen for the orange juice and Coca-Cola groups, possibly due to the low pH in this beverages.…”
Section: Discussionmentioning
confidence: 65%
“…This has been attributed to its sensitivity to manipulation and polymerization shrinkage resulting in a potential avenue of microleakage. 16,17 Burrow et al reported that numerous air inclusions were found within the glass ionomer cement. 18 Xie et al reported that the SEM image of glass ionomer cement showed an obvious marginal gap at the tooth-restoration interface.…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
“…Pathway of the fluid from the oral cavity into the tooth through the restorative material is known as microleakage. 2 It is of great significance for dentists since it occurs around provisional temporary restorations. 2,3 Therefore, treated teeth should be restored with permanent restorations as soon as possible to avoid coronal leakage.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is of great significance for dentists since it occurs around provisional temporary restorations. 2,3 Therefore, treated teeth should be restored with permanent restorations as soon as possible to avoid coronal leakage. 4 If permanent restoration is not possible in the immediate future, temporary filling should be done in such a way that it seals the coronal portion of the teeth hermetically and should have marginal sealing properties.…”
Section: Introductionmentioning
confidence: 99%